2019
DOI: 10.1103/physrevlett.122.030403
|View full text |Cite
|
Sign up to set email alerts
|

Using Polarons for sub-nK Quantum Nondemolition Thermometry in a Bose-Einstein Condensate

Abstract: We introduce a novel minimally-disturbing method for sub-nK thermometry in a Bose-Einstein condensate (BEC). Our technique is based on the Bose-polaron model; namely, an impurity embedded in the BEC acts as the thermometer. We propose to detect temperature fluctuations from measurements of the position and momentum of the impurity. Crucially, these cause minimal back-action on the BEC and hence, realize a non-demolition temperature measurement. Following the paradigm of the emerging field of quantum thermometr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 56 publications
1
82
0
Order By: Relevance
“…a two-level system, may interact with a sample system in a thermal state, and subsequently be measured to estimate the temperature. If the probe reaches thermal equilibrium with the sample, or a nonequilibrium steady state, optimal designs of the probe and of the probesystem interaction can be determined [13][14][15][16][17][18]. Outside of the steady state regime, it was found that access to the transient probe dynamics may outperform the steady-state protocols [19][20][21], that dynamical control acts as a resource [22][23][24], and that thermometry can in some cases be mapped to a phase estimation problem [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…a two-level system, may interact with a sample system in a thermal state, and subsequently be measured to estimate the temperature. If the probe reaches thermal equilibrium with the sample, or a nonequilibrium steady state, optimal designs of the probe and of the probesystem interaction can be determined [13][14][15][16][17][18]. Outside of the steady state regime, it was found that access to the transient probe dynamics may outperform the steady-state protocols [19][20][21], that dynamical control acts as a resource [22][23][24], and that thermometry can in some cases be mapped to a phase estimation problem [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Under certain regularity assumptions, the QFI matrix encodes the ultimate precision bounds on the estimation of unknown parameters encoded in a density matrix (know as quantum Cramer-Rao bounds), while the SLDs and their commutators determine whether such bounds may be saturated with physically realizable measurements [5,6]. The associated applications are plenty, including phase and frequency estimation [4,[7][8][9][10][11][12][13][14][15][16][17], estimation of noise parameters [18][19][20][21][22][23], joint estimation of unitary and/or noisy parameters [24][25][26][27][28][29][30][31], sub-wavelength resolution of optical sources [32][33][34][35][36][37][38], nano-scale thermometry [39][40][41][42][43][44][45], and estimation of Hamiltonian parameters in the presence of phase-transitions [46][47][48]. The most common approach for ...…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, reducing the bath size will allow following the transition from a Markov to a non-Markov bath, shedding new light on the microscopic quantum dynamics for system-bath entanglement [34]. Finally, our experimental system also paves the way to local probing of quantum gases or employing collective interaction effects [35].…”
mentioning
confidence: 99%